Bone mineral density and specific physical performance in Korean national amateur male boxers - Yoon, D. H.; Song, H.-S.; Kim, K.-J. (International Journal of Applied Sports Sciences, 2019)
Background: The objective of this study was to investigate the relationships between bone mineral density, the level of anaerobic capacity and muscle strength in Korean national amateur male boxers. Methods: We carried out a cross-sectional population-based study where fifty-six Korean national amateur male boxers were enrolled. The participants` whole-body bone and regional mineral density (BMD) and bone mineral content (BMC) were assessed using dual-energy X-ray absorptiometry as the main outcome. The anaerobic capacity was assessed using the Upper and lower Wingate test, and muscle strength was assessed using Isokinetic muscle strength and Maximal strength. Results: Of the fifty-six boxer, 37.5% were classified as LWC, 32.1% as MWC, and 30.3% as HWC. Linear regression analyses showed that the severity of bone variable was associated with upper and lower-body anaerobic capacity. Isokinetic muscle strength and Maximal strength were positively associated with bone variables. Conclusions: Within athletes of Korean national amateur male boxers, anaerobic capacity, and muscle strength measurements were positively associated with bone variables. Further research is needed to elucidate mechanisms underlying this positive association that is, undertaking studies involving effective exercise and nutrition supplements treatments, and developing the study designs to facilitate analysis of this relationship.